Growth, yield attributes and phytochemical properties of chia seed (Salvia hispanica) under varying plant densities: Plant Density Effects on Chia Seed Traits - Shahid, SB; Akter, M (Journal of the Sylhet Agricultural University, 2025)
Chia (Salvia hispanica L.) is a diminutive seed of an annual herbaceous plant. In recent years, the utilization of chia seeds has exhibited a marked increase due to their maximal nutritional and therapeutic values. An experiment was conducted at the Agronomy Research field in the Department of Agronomy and Haor Agriculture, Sylhet Agricultural University (SAU), Sylhet, from 16 November 2022 to 12 April 2023. The objective of this study was to ascertain the growth, yield quality, and phytochemical characteristics of Chia seeds at varying plant densities. The tests were conducted in Randomized Complete Block Design (RCBD) with four replicates. Plant population per unit area regarded as treatments T1 =120 m-2 and T2 = 60 m-2. The collected data were evaluated statistically using the R program (version R 4.2.3). The tallest plant height (94.08cm) from T1, maximum count of inflorescence plant-1 (42.11) in T2, highest number of leaves plant-1 (79.60), highest number of branches plant-1 (61.83) was recorded until harvest in T1. The highest seed yield (9.32 Kg/ha), 1000 seed weight (1.38 g) were also recorded in T2 and T1. Additionally other yield attributes such as seeds/floret, floret/inflorescence, number of inflorescence/plants etc. were also found in T1 & T2. Chia seed's overall phenolic content 11.79 mg GAE/g and total flavonoid content 13.37 mg QE/g were both measured after harvest from both treatments. Further study and agricultural advancements will contribute to the cultivation and use of chia seeds in a variety of applications. However, further investigation is necessary to elucidate the bioavailability of chia seeds and the particular extraction procedures related compounds. J. Sylhet Agril. Univ. 11(2): 63-74, 2024